Loss of β-cell identity and dedifferentiation, not an irreversible process? - Patel, Sumit; Remedi, Maria S. (Frontiers in Endocrinology, 2024)
Type 2 diabetes (T2D) is a polygenic metabolic disorder characterized by insulin resistance in peripheral tissues and impaired insulin secretion by the pancreas. While the decline in insulin production and secretion was previously attributed to apoptosis of insulin-producing β-cells, recent studies indicate that β-cell apoptosis rates are relatively low in diabetes. Instead, β-cells primarily undergo dedifferentiation, a process where they lose their specialized identity and transition into nonfunctional endocrine progenitor-like cells, ultimately leading to β-cell failure. The underlying mechanisms driving β-cell dedifferentiation remain elusive due to the intricate interplay of genetic factors and cellular stress. Understanding these mechanisms holds the potential to inform innovative therapeutic approaches aimed at reversing β-cell dedifferentiation in T2D. This review explores the proposed drivers of β-cell dedifferentiation leading to β-cell failure, and discusses current interventions capable of reversing this process, thus restoring β-cell identity and function.